The Appropriate Use of Neurostimulation: New and Evolving Neurostimulation Therapies and Applicable Treatment for Chronic Pain and Selected Disease States. Issue 6 (August 2014) - Deer, Timothy R.; Krames, Elliot; Mekhail, Nagy; Pope, Jason; Leong, Michael; Stanton‐Hicks, Michael; Golovac, Stan; Kapural, Leo; Alo, Ken; Anderson, Jack; Foreman, Robert D.; Caraway, David; et al.
<x xml:space="preserve">Abstract</x> Introduction The International Neuromodulation Society (INS) has determined that there is a need to provide an expert consensus that defines the appropriate use of neuromodulation technologies for appropriate patients. The Neuromodulation Appropriateness Consensus Committee (NACC) was formed to give guidance to current practice and insight into future developments. Methods The INS executive board selected members of the international scientific community to analyze scientific evidence for current and future innovations and to use clinical experience to fill in any gaps in information. The NACC used PubMed and Google Scholar to obtain current evidence in the field and used clinical and research experience to give a more complete picture of the innovations in the field. Results The NACC has determined that currently approved neurostimulation techniques and technologies have expanded our ability to treat patients in a more effective and specific fashion. Despite these advances, the NACC has identified several additional promising technologies and potential applications for neurostimulation that could move this field forward and expand the applicability of neuromodulation. Conclusions The NACC concludes that the field of neurostimulation is an evolving and rapidly changing one that will lead to improved patient access, safety, and outcomes.